2015
DOI: 10.1016/j.jdiacomp.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABC (HbA1c, blood pressure, LDL-cholesterol) goal attainment with depression and health-related quality of life among adults with type 2 diabetes

Abstract: The relationship between simultaneous ABC goal attainment, depression and HRQoL is complex. Patients with T2DM unable to meet ABC goals may benefit from increased contact with health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…In a Norwegian study among schizophrenic ( n = 344) and nonschizophrenic groups ( n = 308), depression was related to LDL and TC levels, while in another study it was shown that depression was associated with elevated levels of several inflammatory cytokines [29-31]. In contrast to our results, Shah et al [32] reported that there was no association of HbA 1c , blood pressure, and LDL cholesterol with depression in adults with type 2 diabetes mellitus. The reason for the conflict in results between our study and this previous study may stem from using different questionnaires to assess depression (i.e., Patient Health Questionnaire-9 [PHQ-9] vs. DASS-21).…”
Section: Discussioncontrasting
confidence: 99%
“…In a Norwegian study among schizophrenic ( n = 344) and nonschizophrenic groups ( n = 308), depression was related to LDL and TC levels, while in another study it was shown that depression was associated with elevated levels of several inflammatory cytokines [29-31]. In contrast to our results, Shah et al [32] reported that there was no association of HbA 1c , blood pressure, and LDL cholesterol with depression in adults with type 2 diabetes mellitus. The reason for the conflict in results between our study and this previous study may stem from using different questionnaires to assess depression (i.e., Patient Health Questionnaire-9 [PHQ-9] vs. DASS-21).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we were able to distinguish duration with type 2 diabetes as a diagnosis and determined that time with the disease is an important distinction to make when considering the disablement process due to physiological processes associated with the disease (Otiniano et al, 2012; Lorenzo et al, 2012; Xiang et al, 2013). Moreover, there is now growing evidence that the longer a person lives with type 2 diabetes, the greater the incidence of depression and other mental health conditions (Ell et al, 2015; Shah et al, 2015). Therefore, the findings from this study are novel and demonstrate that type 2 diabetes is associated with both progression and onset of disability, with more severe increases in disability for Mexican Americans who have had type 2 diabetes for longer periods of time.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Length of time since diagnosis of type 2 diabetes reflects the damage caused by long-term elevated blood sugar (Otiniano et al, 2012) and insulin resistance (Lorenzo et al, 2012; Xiang et al, 2013). Moreover, there is now growing evidence that the longer a person lives with type 2 diabetes, the greater the incidence of depression and other mental health conditions (Ell et al, 2015; Shah et al, 2015). …”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HbA1c monitoring should be performed routinely for all patients with DM, with a target of <7% in non-pregnant adult patients [6]. HbA1c levels are influenced by gender, race, health insurance, DM duration, physical activity, and language understanding, whereas marital status, self-control of glucose, type of DM therapy, and antihypertensive and anticholesterol drug use do not significantly affect this index [6][7][8]. QoL is affected by age, gender, race, comorbidities, occupational status, and educational level [6].…”
Section: Introductionmentioning
confidence: 99%